PENGARUH KOMBINASI EKSTRAK TERPURIFIKASI HERBA ARTEMISIA (Artemisia annua (L.)) DAN HERBA SAMBILOTO (Andrographis paniculata (Burm.f) Nees) TERHADAP KADAR GLUKOSA DARAH PADA TIKUS DIABETES MELLITUS TIPE 2 RESISTEN INSULIN - Kiki Herliyanti; Yuvianti Dwi Franyoto; Etty Sulistyowati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2014)
ABSTRACTInsulin resistance is a common condition that is believed to play a major role in the pathogenesis of the metabolic syndrome, obesity and type 2 diabetes mellitus, and heart disease. The purpose of this study was to determine the antidiabetic activity mellitus combination of purified extract of bitter herbs and artemisia herb in rats with type 2 diabetes mellitus insulin resistance compared with the effect of each extract.Test activity of purified extract of bitter herbs, herbal extracts purified artemisia and combinations thereof done by grouping test animals which have been declared insulin resistance is divided into 7 groups, Group I: a combination of purified extract of bitter herbs 390.9 mg / kg and 83.56 mg of the herb artemisia / kg; Group II: a combination of purified extract of bitter herbs 651.5 mg / kg and herb artemisia 41.7 mg / kg; Group III: purified extract of bitter herbs single dose of 651.5 mg / kg rat; Group IV : purified extract of bitter herbs single dose of 1303 mg / kg, po; Group V: purified extract of the herb artemisia single dose 41.78 mg / kg, po; Group VI: purified extract of the herb artemisia single dose 83.56 mg / KgBW , po; Group VII: positive control (given metformin dose of 45 mg / kg, po); Group VIII: negative control (CMC-Na was given 1%, po). Then the results were analyzed with SPSS 16 statistical test.The percentage decrease preprandial blood glucose levels of administration of a single dose of artemisia extract 83.56 mg / KgBW better than the combination of bitter and herbal28extracts artemisia, while the percentage reduction in postprandial glucose levels in the administration of a combination of extracts of bitter herbs bitter dose of 651.5 mg / kg BB artemisia herb and 41.7 mg / kg better than the extract of bitter herbs and herbal extracts artemisia singly.Keywords: bitter herbs, Artemisia herb, diabetes mellitus, glucose levels